EFFECT OF SITAGLIPTIN ON LIPID PROFILE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS. : JPUMHS;2024:14:03,26-31 http://doi.org/10.46536/jpumhs/2024/14.03.531 - Farzana Memon1, Hajira Naila Rahu2, Muhammad Azhar Mughal3, Nasrullah Aamer4, Zahira Yousuf Memon5, Rukhsana Malik6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT BACKGROUND: Dyslipidemia has been identified as a major risk factor for the development of macrovascular disease; hence, disturbed lipid metabolism and altered serum lipid levels exacerbate the chances of cardiovascular disease and stroke. Sitagliptin, one of the emerging antidiabetic drugs was selected to investigate its effect on the lipid profile in type 2 diabetes. METHODS: This prospective study was conducted on patients diagnosed with type 2 diabetes. The patients were recruited according to the inclusion and exclusion criteria and were monitored for a period ranging from 18 to 36 weeks. Blood samples were taken and analyzed for lipid and blood parameters using the standardized enzymatic method. A paired sample t-test and chi-square test were applied to identify the mean difference in pre- and post-findings using SPSS version 15. The level of significance was set at a p-value of ≤ 0.05. RESULTS: Out of 110 patients, only 100 were selected for the study. Among these, males accounted for 54.50% and females for 45.50%, with a mean age of 50.35 years. The mean fasting blood glucose level prior to therapy was 163.65±32.0 mg/dl, and post-therapy it was 106.20±17.74 mg/dl. At baseline, HbA1C was 9.08±0.97%, which reduced to 6.26±0.87% after therapy. After 36 weeks of treatment with sitagliptin, triglycerides were reduced from 291.32±71.58 to 145.83±36.18 mg/dl. Initially, total cholesterol was found to be 250.30±57.71 mg/dl, which decreased to 131.89±12.80 mg/dl. Upon further analysis, VLDL-C changed from 35.98±7.65 mg/dl to 24.70±7.71 mg/dl. LDL-C levels showed a highly significant reduction from baseline 136.98±20.77 to 119.87±9.24 mg/dl, while HDL-C was found to have increased to 43.63±7.21 mg/dl from 25.38±5.33 mg/dl. CONCLUSION: The results showed statistical significant difference in lipid and blood profiles after treatment with sitagliptin for 36 weeks. It significantly reduced the levels of triglycerides, cholesterol, LDL-C, and VLDL-C, while also improving HDL-C levels.